HOW TO DEAL WITH A TAX AUDIT PROCESS - Valencia Gutiérrez, Adolfo (2010)
Accounting professionals, as advisers and consultants in tax, has become a priority that their clients, employers and taxpayers in general, satisfy their tax obligations promptly to avoid unnecessary and wasteful contingencies. Therefore the duty of the accounting professional your clients have if possible a regular tax situation fully comply with all formal and substantial requirements and its fiscal condition does not fall within the conduct legally classified as infractions or tax crimes. With this background outlined some general aspects that must take into account the professional accountant before the fact may face a fiscal review process when the tax authority so requires, using its powers of oversight, is how the accountant should highlight its role in protecting the interests of the taxpayer, enforcing their rights and resorting to various means of defense, when it became clear excesses or errors, by filing the relevant shares before the corresponding which provides the constitutional tax law.